MR-IMAGING IN DIAGNOSTICS OF FOCAL LIVER LESIONS - S. S. Bagnenko; G. E. Trufanov; I. S. Zheleznyak (Вестник хирургии имени И.И. Грекова)
The authors determined the efficacy of main methods of MR-imaging and their part in differentiated diagnostics of focal liver lesions. There were examined 256 patients and 414 liver lesions were analyzed. It was shown that the efficacy of conventional research without application of contrast medium was very limited (efficacy of mathematical model 58%). The data obtained during dynamic contrast enchancement (efficacy of the model 67%) were the basis for differentiated diagnostics for majority of nosological forms. The investigation using hepatotropic contrast medium had the greatest possibilities (efficacy of the model 80%). MR-diffusion is the effective procedure for visualization of focal liver lesions, but its possibilities in differentiated diagnostics is limited.